2016
DOI: 10.3329/ajmbr.v2i2.29072
|View full text |Cite
|
Sign up to set email alerts
|

Deep placement of N fertilizers influences N use efficiency and yield of BRRI dhan29 under flooded condition

Abstract: An experiment was conducted at the Soil Science Field Laboratory of Bangladesh Agricultural University, Mymensingh during boro season of 2014 to evaluate the effect of deep placement of nitrogen (N) fertilizers on N use efficiency and yield of BRRI dhan29 under flooded condition. The soil was silt loam in texture having pH 6.27, organic matter content 1.95%, total N 0.136%, available P 3.16 ppm, exchangeable K 0.095 me%, available S 10.5 ppm and EC 348 μS cm -1 . . All the treatments except T 6, T 7 and T 8 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…NUE represents the response of rice plant in terms of grain yield to N fertilizer. The maximum value of NUE (44.01 kg grain yield increase per kg N applied) was obtained for T 4 which is similar with the findings of (Hasan et al, 2016;Huda et al, 2016). Whereas, the minimum value was found in T 2 where, 14.46 kg grain yield increases for per kg N applied.…”
Section: Nitrogen Use Efficiency (Nue)supporting
confidence: 85%
See 1 more Smart Citation
“…NUE represents the response of rice plant in terms of grain yield to N fertilizer. The maximum value of NUE (44.01 kg grain yield increase per kg N applied) was obtained for T 4 which is similar with the findings of (Hasan et al, 2016;Huda et al, 2016). Whereas, the minimum value was found in T 2 where, 14.46 kg grain yield increases for per kg N applied.…”
Section: Nitrogen Use Efficiency (Nue)supporting
confidence: 85%
“…Further, nitrogen fertilizer is costly, thus it is important to minimize the losses of nitrogen fertilizers and maximize the economic utility. Nitrogen use efficiency (NUE) of different rice cultivars such as BRRI dhan1 (Haque and Haque, 2016), BRRI dhan28, BRRI dhan36 (Alim, 2012), BRRI dhan29 (Hasan et al, 2016;Alam et al, 2010) has been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported that slow-released N fertilizer is an effective management strategy for improving NUE in rice [9,33,34]. When prilled urea is used in flooded conditions, it quickly hydrolyzes and releases more NH 4 + -N in the soil and water over the course of a few days, which promotes N loss through denitrification and volatilization.…”
Section: Discussionmentioning
confidence: 99%
“…However, urea deep placement (UDP) was already proven to reduce nitrogen losses by as much as 50% than the broadcast method (Huda et al, 2016). The concentration of NH 4 -N in flood water decreases by the deep placement of USG than the broadcast application of PU (Hasan et al, 2016). When compared to a split PU application, placing USG at 8-10 cm depth in the soil can save 30% nitrogen and enhance nutrient uptake, improve soil health, and eventually accelerates crop production (Rahman and Barmon, 2015;Islam et al, 2019).…”
Section: Introductionmentioning
confidence: 99%